Prognostic value of respiratory quotients in severe polytrauma patients with nutritional support - Patkova, Anna; Joskova, Vera; Havel, Eduard; Najpaverova, Simona; Uramova, Daniela; Kovarik, Miroslav; Zadak, Zdenek; Hronek, Miloslav (Nutrition, 2018)
OBJECTIVE: The association between energy metabolism and prognosis in polytrauma patients has not yet been defined. The aim of this study was to describe energy metabolism and analyze the prognostic value of respiratory quotient (RQ) and nonprotein respiratory quotient (npRQ) in fasting polytrauma patients (fPP) and polytrauma patients with nutritional support (nsPP). METHODS: Twenty-two polytrauma patients (before and after parenteral nutrition administration) and 22 healthy controls (after overnight fasting) were examined on day 4 (median) after admission to the intensive care unit. To evaluate energy expenditure in nsPP and resting energy expenditure in fPP and controls with RQ and npRQ in all groups, we used indirect calorimetry. With regression analysis, the descriptive models of intensive care unit (ICU) length of stay (LOS) and mechanical ventilation time (VT) were derived. RESULTS: RQ and npRQ were significantly lower in fPP than in controls (P < 0.05 and P < 0.01, respectively) and in nsPP (P < 0.05). In nsPP, relationships between RQ or npRQ and the ICU LOS or mechanical VT were demonstrated (P < 0.0001, r = -0.78 for RQ and VT; P < 0.0001, r = -0.78 for npRQ and VT; P < 0.001, r = -0.69 for RQ and LOS; P < 0.001, r = -0.72 for npRQ and LOS). CONCLUSIONS: RQ and npRQ parameters measured by indirect calorimetry in polytrauma patients with parenteral nutrition on the fourth day of ICU stay related to clinical outcomes such as duration of mechanical ventilation and ICU LOS.
Keywords: Respiratory Function Tests; prospektivní studie; jednotky intenzivní péče; omezení příjmu potravy; Basal Metabolism; Length of Stay; Humans; lidé; umělé dýchání; regresní analýza; lidé středního věku; respirační funkční testy; Treatment Outcome; Time Factors; Middle Aged; energetický metabolismus; nepřímá kalorimetrie; Multiple Trauma; časové faktory; Pilot Projects; pilotní projekty; Female; Male; Adult; Prospective Studies; Energy Metabolism; prognóza; Prognosis; délka pobytu; výsledek terapie; Intensive Care Units; Respiration, Artificial; parenterální výživa; mužské pohlaví; ženské pohlaví; polytrauma; Parenteral Nutrition; bazální metabolismus; dospělí; Fasting; Regression Analysis; Calorimetry, Indirect